The Problematics of the Implementation of the Dominus Litis - Yusni, Muhammad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Public prosecutors have the authority to control criminal cases, examine the results of investigators' examinations, or filter case files regarding the completeness of requirements and eligibility standards to be delegated to court. This principle is called dominus litis. Etymologically dominus (Latin), which means owner, litis means case or lawsuit. In this context, the public prosecutor as dominus litis is the owner of a criminal case submitted to the court for trial. The problem of applying the dominus litis principle from the perspective of the prosecutor's office raises many problems, which can hinder a simple, fast, and low cost judicial process. The back and forth of criminal case files between public prosecutors and investigators is not a strange thing in this context, the slow process of criminal justice is protracted, tiring, and even unclear, and creates injustice for justice seekers, and so on.